MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERFIKIR KREATIF DALAM MENULIS TEKS PUISI DI SMP - Poni Fera; Kamarudin Kamarudin; Rustam Rustam (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2022)
This study aims to explain the implementation of the project based learning (PjBL) learning model in learning to write poetry texts. The research method used is a qualitative method, this type of research is a phenomenological research type, which is a study that seeks to articulate the